Ultrafast charge processing method for improving conductivity of slurry

The ultrafast charge processing method addresses conductivity issues in conductive paste by regulating the conductive network structure through high voltage discharge, achieving improved conductivity and distribution, thus enhancing the performance of solar cells and sensors.

CN119207890AActive Publication Date: 2024-12-27SOUTHEAST UNIV

Patent Information

Application Number
CN202411380708.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The conductivity of conductive paste is limited by uneven distribution of conductive particles and poor particle contact, leading to suboptimal performance in applications such as solar cells and sensors.

Method used

An ultrafast charge processing method involving mixing conductive particles with a solvent, binder, and additive, printing on a substrate, drying and curing, and applying a high voltage discharge to regulate the conductive network structure.

Benefits of technology

Significantly improves conductivity by reducing resistivity from 1×10^6 Ω·cm to 1Ω·cm, enhances particle distribution, and lowers production costs and time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069827350000041
    Figure BDA0005069827350000041
  • Figure BDA0005069827350000051
    Figure BDA0005069827350000051
  • Figure BDA0005069827350000061
    Figure BDA0005069827350000061
Patent Text Reader

Abstract

The invention discloses an ultrafast charge processing method for improving the conductivity of slurry, which comprises the following steps of: fully mixing metal particles, an adhesive, a solvent and an additive according to a certain proportion to ensure that the metal particles are uniformly dispersed in the slurry; and the slurry after film formation is subjected to charge discharge, so that the conductivity of the slurry film is remarkably improved. According to the invention, the strong electric field and current generated by charge discharge can change the mutual contact of the conductive particles in the film, so that different effects of regulating and controlling the conductive network are realized, and the resistivity of the slurry film can be regulated and controlled to be reduced from more than 1 * 10 < 6 > omega.cm to 1 omega.cm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrical machining method, in particular to an ultrafast charge machining method capable of improving conductive slurry, and belongs to the technical field of electrical machining. Background Art

[0002] Conductive paste is widely used in solar cells, photovoltaic modules, sensors and other high-tech fields. Its conductive properties directly affect the performance of end products. However, in practical applications, the conductivity of the paste is often limited by factors such as uneven distribution of conductive particles in the paste and poor contact between particles. Therefore, how to effectively improve the conductivity of conductive paste has become an important research task.

[0003] Traditional methods to improve the conductive properties of slurries include optimizing the material, shape and size of conductive particles, improving slurry formulations, and using special coating and sintering processes. However, most of these methods are complex, costly, and have limited effects, and have great limitations in practical applications. Storing charge in a capacitor and then releasing the charge to an object can produce an effect with ultra-fast high voltage and high current. This effect can effectively control the microstructure of the material under the action of current or voltage and improve the electrical contact between conductive particles. At the same time, a conductive network of particles with conductive contact is formed for the slurry. Compared with traditional methods, charge discharge machining technology can not only significantly improve the conductivity of conductive slurries, but also has a simple process and low cost, and has broad application prospects.

[0004] Therefore, proposing a new method of improving the conductivity of conductive paste by ultrafast charge processing technology not only has important theoretical significance, but also has great practical application value. The realization of this technology is expected to promote the application and development of conductive paste in the fields of sensors, solar cells and electronic devices, improve the performance and reliability of related products, and promote technological innovation in the field of materials science and engineering, which has important economic and social significance. In future development, this technology is expected to play an important role in more high-tech fields and provide strong support for scientific and technological progress and industrial development. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide an ultrafast charge processing method for improving the conductivity of slurry.

[0006] Technical solution: The ultrafast charge processing method for improving the conductivity of slurry described in the present invention comprises the following steps:

[0007] (1) uniformly mixing the conductive particles with a solvent, a binder and an additive to obtain a mixed slurry;

[0008] (2) printing the mixed slurry evenly on the substrate, drying and curing it to form a conductive film on the substrate;

[0009] (3) Fix the substrate with the conductive film on the test bench, connect the charge generator to the conductive film, and set the discharge amount and discharge time as required;

[0010] (4) Triggering the charge generator to discharge the charge into the conductive film, causing its resistivity to change.

[0011] Furthermore, in step (1), the conductive particles are one or more of metal conductive particles or carbon material conductive particles.

[0012] Furthermore, the metal conductive particles are silver, copper, aluminum or nickel, and the carbon material conductive particles are carbon nanotubes, carbon black or graphene.

[0013] Furthermore, in step (1), the particle size of the conductive particles is 1-10 μm.

[0014] Furthermore, in step (1), the solvent is one or more of ethanol, isopropanol, butanone, DBE, terpineol, diethylene glycol butyl ether, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, ethylene glycol butyl ether acetate, ethylene glycol ethyl ether acetate, propylene glycol methyl ether, ethyl acetate, and dichloromethane.

[0015] Furthermore, in step (1), the adhesive is a slurry adhesive, which is one or more of a polymer resin, an inorganic glass powder, a silicon material, etc., such as one or more of epoxy resin EPON 828, EPON 1001F, an acrylic resin, and a polyester resin.

[0016] Furthermore, in step (1), the additive is one or more of polyvinyl pyrrolidone, polyethylene glycol, hydroxypropyl methylcellulose, carbomer, silicone oil, polyether modified silicone oil, sulfosuccinate, silica nanoparticles, alkylphenol polyoxyethylene ether, 2,6-di-tert-butyl-p-cresol, benzophenone, nano zinc oxide, silane coupling agent, titanate coupling agent, isocyanate curing agent, dicyandiamide, modified dicyandiamide, acid anhydride, boron trifluoride monoethylamine, amino resin, and sintering accelerator.

[0017] Furthermore, the silane coupling agent is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane.

[0018] Furthermore, the mass ratio of metal conductive particles, solvent, adhesive and additive is 60-95:8-30:5-15:1-5; the mass ratio of carbon material conductive particles, solvent, adhesive and additive is 1-5:8-30:60-90:1-5.

[0019] Furthermore, in step (2), the substrate is a polytetrafluoroethylene board or a PVC board.

[0020] Furthermore, in step (2), the printing method is one of screen printing, inkjet printing, 3D printing, photovoltaic printing or transfer printing.

[0021] Furthermore, in step (2), the drying and curing temperature is 80 to 1000° C., preferably 100 to 500° C., and the drying and curing time is the time required for the slurry to be completely cured, generally 1 to 120 min, preferably 30 min.

[0022] Furthermore, in step (2), the thickness of the conductive film is 0.1 to 2 mm.

[0023] Furthermore, in step (3), the charge is directly applied to the conductive paste film.

[0024] Furthermore, in step (3), the discharge parameters are: discharge voltage 1 to 100 kV, and discharge time less than 10 μs.

[0025] Furthermore, in step (3), the high voltage capacitor is charged with high voltage to form a charge generator, and the discharge time of the charge in the capacitor is controlled by a discharge relay.

[0026] Furthermore, in step (4), the change in resistivity is caused by a change in the structure of the network of conductive particles in contact with each other in the slurry.

[0027] Furthermore, in step (4), the resistivity of the slurry can be adjusted to vary from 1×10 6 Above Ω·cm is reduced to 1Ω·cm.

[0028] Principle of the invention: When a discharge voltage is applied to the conductive slurry, the conductive particles in the slurry vibrate, twist, rotate or move due to Maxwell stress, causing the structure of its conductive network to change. By adjusting factors such as peak voltage and discharge time, the conductive network structure in the slurry can be regulated, and then the conductivity of the conductive slurry can be regulated.

[0029] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0030] (1) The method of the present invention can make the conductive particles in the slurry contact with each other better through ultrafast charge processing, causing the resistivity of the slurry to decrease significantly. The range of the resistivity of the slurry can be adjusted from 1×10 6 Ω·cm or more to 1Ω·cm, and the best can reach 2.5×10 6 Ω·cm dropped to 1.5Ω·cm.

[0031] (2) The method of the present invention makes the conductive particles in the slurry more evenly distributed, thereby improving the quality of the final product.

[0032] (3) The method of the present invention is easy to operate and reduces production time and cost. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described below in conjunction with embodiments.

[0034] Example 1

[0035] The present invention discloses an ultrafast charge processing method for improving the conductivity of slurry, comprising the following steps:

[0036] (1) 8.2 g of silver powder (particle size of 5 μm), 0.8 g of isobutyl alcohol, 0.5 g of epoxy resin EPON828 and 0.5 g of γ-aminopropyltriethoxysilane were uniformly mixed in a mass ratio of 82:8:5:5 to obtain a mixed slurry;

[0037] (2) The mixed slurry was evenly printed on a 20 cm × 20 cm PVC substrate by inkjet printing;

[0038] (3) The substrate printed with the mixed slurry was dried and cured at 150°C for 30 min to form a 1 mm thick conductive film, and its initial resistivity was recorded (see Table 1);

[0039] (4) Fix the conductive film on the test bench, charge the high-voltage capacitor to form a charge generator, control the charge discharge time through the discharge relay, and connect the output end of the charge generator to the conductive film. Set the discharge voltage and time, and set the corresponding parameters according to Table 1.

[0040] (5) Trigger the charge generator to discharge the conductive film, causing its resistivity to change. Record its final resistivity. The results are shown in Table 1.

[0041] Embodiment 2-4

[0042] The experimental process is the same as that of Example 1, except that the mass ratios of silver, isobutyl alcohol, EPON 828 and γ-aminopropyltriethoxysilane are different. The basic steps are the same as those of Example 1. The specific parameters are shown in Table 1. The results are shown in Table 1.

[0043] Table 1 Resistivity improvement effect of different mass ratios of silver powder, isobutyl alcohol, EPON 828 and γ-aminopropyltriethoxysilane

[0044]

[0045] As shown in Table 1, when the voltage is 100 kV and the discharge time is 0.5 μs, the resistivity of the conductive paste decreases significantly, and the maximum value can be increased from 2.5×10 6 Ω·cm dropped to 1.1Ω·cm.

[0046] Example 5

[0047] The experimental process is the same as that of Example 1, except that the conductive particles are changed to copper, the solvent is changed to diethylene glycol butyl ether, the additive is changed to isocyanate curing agent, and different discharge parameters are used, specifically including the following steps:

[0048] (1) 6.5 g of copper powder (particle size of 5 μm), 1.5 g of diethylene glycol butyl ether, 1.5 g of EPON 828 and 0.5 g of isocyanate curing agent were uniformly mixed in a mass ratio of 65:15:15:5 to obtain a mixed slurry;

[0049] (2) The mixed slurry was evenly printed on a 20 cm × 20 cm PVC substrate using an inkjet printing method;

[0050] (3) The substrate printed with the mixed slurry was dried and cured at 150°C for 30 min to form a 1 mm thick conductive film, and its initial resistivity was recorded (see Table 2);

[0051] (4) Fix the conductive film on the test bench, charge the high-voltage capacitor to form a charge generator, control the charge discharge time through the discharge relay, connect the output end of the charge generator to the conductive film, set the discharge voltage and time, and set the corresponding parameters according to Table 2.

[0052] (5) Trigger the charge generator to discharge the conductive film, causing its resistivity to change. Record its final resistivity. The results are shown in Table 2.

[0053] Embodiment 6-8

[0054] The experimental process is the same as that of Example 5, except that the mass ratios of copper powder, diethylene glycol butyl ether, EPON 828 and isocyanate are different. The basic steps are the same as those of Example 5. The specific parameters are shown in Table 2, and the results are shown in Table 2.

[0055] Table 2 Resistivity reduction effect of different mass ratios of copper powder, diethylene glycol butyl ether, EPON 828 and isocyanate curing agent

[0056]

[0057] As can be seen from Table 2, when the voltage is 80 kV and the discharge time is 1 μs, the resistivity of the conductive paste decreases significantly, and the maximum value can be increased from 3.2×10 7 Ω·cm dropped to 4.2Ω·cm.

[0058] Example 9

[0059] The experimental process is the same as that of Example 1, except that the solvent is changed to diethylene glycol butyl ether, the binder is changed to acrylic resin, the additive is changed to polyvinyl pyrrolidone, and different discharge parameters are used, specifically including the following steps:

[0060] (1) 7 g of silver powder (particle size of 5 μm), 1 g of diethylene glycol butyl ether, 1.5 g of acrylic resin and 5 g of polyvinyl pyrrolidone were uniformly mixed in a mass ratio of 70:10:15:5 to obtain a mixed slurry;

[0061] (2) The mixed slurry was evenly printed on a 20 cm × 20 cm PVC substrate using an inkjet printing method;

[0062] (3) The substrate printed with the mixed slurry was dried and cured at 120°C for 30 min to form a 1 mm thick conductive film, and its initial resistivity was recorded (see Table 3);

[0063] (4) Fix the conductive film on the test bench, charge the high-voltage capacitor to form a charge generator, control the charge discharge time through the discharge relay, connect the output end of the charge generator to the conductive film, set the discharge voltage and time, and set the corresponding parameters according to Table 3.

[0064] (5) Trigger the charge generator to discharge the conductive film, causing its resistivity to change. Record its final resistivity. The results are shown in Table 3.

[0065] Examples 10-12

[0066] The experimental process is the same as that of Example 9, except that the mass ratios of silver, diethylene glycol butyl ether, acrylic resin and polyvinyl pyrrolidone are different. The basic steps are the same as those of Example 9. The specific parameters are shown in Table 3. The results are shown in Table 3.

[0067] Table 3 Resistivity reduction effect of different mass ratios of silver powder, diethylene glycol butyl ether, acrylic resin and polyvinyl pyrrolidone

[0068]

[0069] It can be seen from Table 3 that when the voltage is 50 kV and the discharge time is 0.5 μs, the resistivity of the conductive paste decreases significantly, and the maximum value can be increased from 2.7×10 8 Ω·cm dropped to 11.9Ω·cm.

[0070] Embodiment 13

[0071] The experimental process is the same as that of Example 1, except that the conductive particles are changed to carbon nanotubes, the solvent is changed to pine alcohol, the binder is changed to low-melting-point glass powder, and different dosages and different discharge parameters are used, specifically including the following steps:

[0072] (1) 0.5 g of carbon nanotubes, 2.5 g of terpineol, 6.5 g of low-melting-point glass powder, and 0.5 g of γ-aminopropyltriethoxysilane were uniformly mixed in a mass ratio of 5:25:65:5;

[0073] (2) The mixed slurry was evenly printed on a 20 cm × 20 cm PVC substrate using an inkjet printing method;

[0074] (3) The substrate printed with the mixed slurry was dried and cured at 180°C for 30 min to form a 1 mm thick conductive film, and its initial resistivity was recorded (see Table 4);

[0075] (4) Fix the conductive film on the test bench, charge the high-voltage capacitor to form a charge generator, control the charge discharge time through the discharge relay, connect the output end of the charge generator to the conductive film, set the discharge voltage and time, and set the corresponding parameters according to Table 4.

[0076] (5) Trigger the charge generator to discharge the conductive film, causing its resistivity to change. Record its final resistivity. The results are shown in Table 4.

[0077] Examples 14-16

[0078] The experimental process is the same as that of Example 13, except that the mass ratios of carbon nanotubes, pineol, low-melting-point glass powder and γ-aminopropyltriethoxysilane are different. The basic steps are the same as those of Example 13. The specific parameters are shown in Table 4, and the results are shown in Table 4.

[0079] Table 4 Resistivity reduction effect of different mass ratios of carbon nanotubes, pineol, low melting point glass powder, and γ-aminopropyltriethoxysilane

[0080]

[0081] It can be seen from Table 4 that when the voltage is 5 kV and the discharge time is 1 μs, the resistivity of the conductive paste decreases significantly, and the maximum value can be increased from 1.7×10 7 Ω·cm dropped to 25.6Ω·cm.

[0082] Comparative Examples 1-4

[0083] The experimental process is the same as that of Example 1-4, except that the voltage is different. The specific parameters and results are shown in Table 5. The results are shown in Table 5.

[0084] Table 5 Resistivity reduction effect of different mass ratios of silver powder, isobutyl alcohol, EPON 828 and γ-aminopropyltriethoxysilane

[0085]

[0086] It can be seen from Table 5 that when the voltage is 0.5 kV and the discharge time is 0.5 μs, the resistivity of the conductive paste only decreases slightly, and the overall resistivity decreases from about 1×10 6 Ω·cm decreased to 10 5 The effect of changing the resistivity is much smaller than that of Examples 1 to 4, which indicates that voltage is an important factor affecting the conductivity of the slurry.

[0087] Comparative Examples 5-8

[0088] The experimental process is the same as that of Example 5-8, except that the discharge time is different. The specific parameters and results are shown in Table 6.

[0089] Table 6 Resistivity reduction effect of different mass ratios of copper powder, diethylene glycol butyl ether, EPON 828 and isocyanate curing agent

[0090]

[0091] It can be seen from Table 6 that when the voltage is 80 kV and the discharge time is 20 μs, the resistivity of the conductive paste decreases slightly, roughly from 1×10 9 Ω·cm decreased to 10 6 The effect of changing the resistivity is much smaller than that of Examples 5-8, indicating that the discharge time is an important factor affecting the conductivity of the slurry.

[0092] Comparative Examples 9-12

[0093] The experimental process is the same as that of Examples 9-12, except that the mass ratios of silver powder: diethylene glycol butyl ether: acrylic resin: polyvinyl pyrrolidone are different. The specific parameters and results are shown in Table 7.

[0094] Table 7 Resistivity reduction effect of different mass ratios of silver powder, diethylene glycol butyl ether, acrylic resin and polyvinyl pyrrolidone

[0095]

[0096] It can be seen from Table 7 that when the voltage is 50 kV and the discharge time is 0.5 μs, the resistivity of the conductive paste decreases slightly, roughly from 1×10 9 Ω·cm decreased to 10 7 The effect of changing the resistivity is much smaller than that of Examples 9-12, indicating that the mass ratio of silver powder: diethylene glycol butyl ether: acrylic resin: polyvinyl pyrrolidone is an important factor affecting the conductivity of the slurry.

[0097] Comparative Examples 13-16

[0098] The experimental process is the same as that of Examples 13-16, except that the mass ratios of carbon nanotubes: terpineol: low-melting-point glass powder: γ-aminopropyltriethoxysilane are different. The specific parameters and results are shown in Table 8.

[0099] Table 8 Resistivity reduction effect of different mass ratios of carbon nanotubes, pineol, low melting point glass powder, and γ-aminopropyltriethoxysilane

[0100]

[0101] It can be seen from Table 8 that when the voltage is 5 kV and the discharge time is 0.1 μs, the resistivity of the conductive paste decreases slightly, roughly from 1×10 8 Ω·cm decreased to 10 7 The effect of changing the resistivity is much smaller than that of Examples 13-16, indicating that the mass ratio of carbon nanotubes: terpineol: low melting point glass powder: γ-aminopropyltriethoxysilane is an important factor affecting the conductivity of the slurry.

[0102] From the above experiments, it can be seen that the mass ratio of raw materials, voltage and discharge time in the method of the present invention can affect the effect of improving the conductivity of the slurry. Finally, it is found that the mass ratio of metal conductive particles, solvents, binders and additives is 60-95:8-30:5-15:1-5; the mass ratio of carbon material conductive particles, solvents, binders and additives is 1-5:8-30:60-90:1-5. When the voltage is 1-100 kV and the discharge time is less than 10 μs, the conductivity of the slurry can be basically increased from 1×10 6 Ω·cm or more and drop to 1Ω·cm.

Claims

1. An ultrafast charge processing method for improving the conductivity of slurry, characterized in that: The following steps are involved: (1) uniformly mixing the conductive particles with a solvent, a binder and an additive to obtain a mixed slurry; (2) printing the mixed slurry evenly on the substrate, drying and curing it to form a conductive film on the substrate; (3) Fix the substrate with the conductive film on the test bench, connect the output end of the charge generator to the conductive film, and set the discharge amount and discharge time as required; (4) Triggering the charge generator to discharge the conductive film, causing its resistivity to change.

2. The ultrafast charge processing method for improving the conductivity of slurry according to claim 1, characterized in that: In step (1), the conductive particles are one or more of metal conductive particles or carbon material conductive particles.

3. The ultrafast charge processing method for improving the conductivity of slurry according to claim 2, characterized in that: The metal conductive particles are silver, copper, aluminum or nickel, and the carbon material conductive particles are carbon nanotubes, carbon black and graphene.

4. The ultrafast charge processing method for improving the conductivity of slurry according to claim 1, characterized in that: In step (1), the adhesive is one or more of polymer resin, inorganic glass powder, silicon material, etc.

5. The ultrafast charge processing method for improving the conductivity of slurry according to claim 1, characterized in that: In step (1), the additive is one or more of polyvinyl pyrrolidone, polyethylene glycol, hydroxypropyl methylcellulose, carbomer, silicone oil, polyether modified silicone oil, sulfosuccinate, silica nanoparticles, alkylphenol polyoxyethylene ether, 2,6-di-tert-butyl-p-cresol, benzophenone, nano zinc oxide, silane coupling agent, titanate coupling agent, isocyanate curing agent, dicyandiamide, modified dicyandiamide, acid anhydride, boron trifluoride monoethylamine, amino resin, and sintering accelerator.

6. The ultrafast charge processing method for improving the conductivity of slurry according to claim 2 or 3, characterized in that: The mass ratio of metal conductive particles, solvent, adhesive and additive is 60-95:8-30:5-15:1-5; the mass ratio of carbon material conductive particles, solvent, adhesive and additive is 1-5:8-30:60-90:1-5.

7. The ultrafast charge processing method for improving the conductivity of slurry according to claim 1, characterized in that: In step (2), the printing method is one of screen printing, inkjet printing, 3D printing, photovoltaic printing or transfer printing.

8. The ultrafast charge processing method for improving the conductivity of slurry according to claim 1, characterized in that: In step (2), the drying and curing temperature is 80 to 1000° C., and the drying and curing time is 1 to 120 minutes; the thickness of the conductive film is 0.1 to 2 mm.

9. The ultrafast charge processing method for improving the conductivity of slurry according to claim 1, characterized in that: In step (3), the charge is directly applied to the conductive film, and the discharge parameters are: discharge voltage 1 to 100 kV, and discharge time less than 10 μs.

10. The ultrafast charge processing method for improving the conductivity of slurry according to claim 1, characterized in that: In step (4), the change in resistivity is caused by the structural change of the contact network of the conductive particles in the slurry. The resistivity of the slurry can be adjusted from 1×10 6 Above Ω·cm is reduced to 1Ω·cm.

Citation Information

Patent Citations

  • Process for the preparation of highly pure dimethyl ether

    EP0560057A1

  • Connecting Solar Cell Tabs To A Solar Cell Busbar And A Solar Cell So Produced

    CN102483969A

  • Method of transparent conducting thin film material heat treatment

    CN103824648A

  • Manufacture method of flexible transparent conductive membrane, and flexible transparent conductive membrane

    CN104851523A

  • Method and device for reducing volume resistivity of carbon-based conductive film

    CN107545958A

Cited By

  • Failure circuit repairing method based on electromagnetic pulse technology

    CN121815566A

  • A method for manufacturing a high-conductivity transparent electrode based on a short-time broadband electromagnetic field

    CN122762390A